Estratégias visando a formação e incorporação de nitreto de boro hexagonal em aços inoxidáveis - Oliveira, Vinicius Antonio de (2021)
There are many examples of the oil relevance in today’s society, such as, manufacturing of materials, fuels production and huge significance on the country's economy. Concerning the exploration of this product some challenges are found, mainly related to the conditions that the equipment are susceptible on the sea environment. Some examples are associated with pipes that are used in drilling and oil exploration, called risers. These pipes are generally made of hot rolled steels and have high corrosion resistance, however, in some situations, they exhibit insufficient wear resistance and high friction coefficient. Our research group in the Materials Engineering Department at Federal University of São Carlos (UFSCar), in partnership with Petrobras, has been developing many researches about this subject and achieving important outcomes. In recent projects it was possible to verify a positive influence on the wear resistance promoted by hard particles (boride) in stainless steels modified with boron addition. On this context, this project aims at keeping the studies and explore the viability of hexagonal boron nitride (h-BN) formation/incorporation in stainless steels. Through the presence of these nitrides in the microstructure, it is expected that the coefficient of friction reduces, resulting in a decrease of the damages caused by contact between the parts involved in the oil exploration process. From scanning electronic microscopy analysis and X-ray diffraction analysis, it was possible to note that some casting process strategies were not efficient related to h-BN formation/incorporation in stainless steel alloys. However, strategies that were related to powder processing appeared to be efficient, being able to open opportunities to produce coatings made of steels alloys in the presence of h-BN and borides in the microstructure.